To eller tre regimenter i den lutherske kaldsetik? - Stenbæk, Jørgen (Religionsvidenskabeligt Tidsskrift, 1990)
Udvikling og aktualitet i luthersk socialetik The article is the result of researches into the catechetical tradition behind the Lutheran ethics of vocation. The interpretation of the fourth commandment in the Lutheran catechesis (“Honour thy father and thy mother”) forms the basis, but the main subject is the Lutheran doctrine of the three status, status ecclesiasticus, politicus and oeconomicus, interpreted as three fields of function, in which the Christian charity is to be practiced, according to the Lutheran tradition of social ethics. In the last part of the article a confrontation is made between the doctrine of the three status and the modern doctrine of human rights.